2023
DOI: 10.1007/s10705-022-10245-x
|View full text |Cite
|
Sign up to set email alerts
|

Potato and soil 15N recoveries from different labelled forage root and shoot

Abstract: An improved understanding of the contribution of a preceding forage crop to a subsequent potato crop can improve nitrogen (N) utilization in potato production. This study used two rotation experiments to estimate the N contribution from labelled shoot and root of red clover (RC, Trifolium pratense), timothy (T, Phleum pratense) and a red clover/timothy mixture (M) to a subsequent potato crop using microplots in the field. Forage crops were grown with 14NH414NO3 and 15NH415NO3 (98 atom %). The residue exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Because microbial carbon and nitrogen cycles are fundamentally linked, and soil capacity and nitrogen mineralization in soils are closely correlated, management practices resulting in soil organic carbon losses significantly impact how much nitrogen can be stored in soils. So, crop yield is effectively harmed when soil organic matter is lost (Whittaker et al 2023). The mean recovery of a single application of nitrogen-15 fertilizer in aboveground sections of crops at all locations was reported to be 5.7-7.1% in the five following growing seasons (excluding the crop fertilized with nitrogen-15).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Because microbial carbon and nitrogen cycles are fundamentally linked, and soil capacity and nitrogen mineralization in soils are closely correlated, management practices resulting in soil organic carbon losses significantly impact how much nitrogen can be stored in soils. So, crop yield is effectively harmed when soil organic matter is lost (Whittaker et al 2023). The mean recovery of a single application of nitrogen-15 fertilizer in aboveground sections of crops at all locations was reported to be 5.7-7.1% in the five following growing seasons (excluding the crop fertilized with nitrogen-15).…”
Section: )mentioning
confidence: 99%
“…The mean recovery of a single application of nitrogen-15 fertilizer in aboveground sections of crops at all locations was reported to be 5.7-7.1% in the five following growing seasons (excluding the crop fertilized with nitrogen-15). Therefore, a cropping system's first crop's average nitrogen-15 fertilizer recovery rate was 44% (Whittaker et al 2023), and in the first five harvests, there was an overall recovery of nitrogen-15 fertilizer of around 50%. The remaining 50% of nitrogen-15 fertilizer would contribute to a sizable soil nitrogen pool, some of which may be lost from the cropping system, assuming that nitrogen-15 in roots had diminished by the sixth growing season (Su et al 2018).…”
Section: )mentioning
confidence: 99%
“…Three papers in this special issue used 15 N tracer methods to study those pathways. Whittaker et al (2023) studied the contribution of shoot and root residues from forage crops to the subsequent crop, in their case potato, by use of 15 N enriched residues from different forage plants. In two experiments they showed that less than 5% of the 15 N in residues were recovered in the potato plants, while the majority was recovered in soil.…”
Section: Fate Of Mineral and Organic Nitrogen Fertilizermentioning
confidence: 99%